Innovations in community-based mental health care: an overview of meta-analyses. (17th November 2022) - Carrà, Giuseppe; Bartoli, Francesco; Capogrosso, Chiara A.; Cioni, Riccardo M.; Moretti, Federico; Piacenti, Susanna; Riboldi, Ilaria; Crocamo, Cristina; Bebbington, Paul E.
Abstract: In the last four decades, mental health services for people with Severe Mental Illness (SMI) have seen asylums replaced by a balanced model of Community Mental Healthcare (CMH). Innovative approaches and strategies in the field of CMH have been extensively researched. However, this research has been hampered by issues limiting their capacity to inform clinicians and policymakers. We conducted an overview of meta-analyses of the effectiveness of innovative CMH models focussing on clinical and psychosocial outcomes in comparisons with standard care in adults with SMI. Based on the 12 eligible studies, we appraised, synthesised and graded the resulting evidence. There was moderate quality evidence that case management, Early Intervention Services (EIS) and caregiver-directed interventions were superior to standard care in reducing hospital admission. In relation to psychosocial outcomes, EIS showed high quality evidence of a small effect on global functioning. There was moderate quality evidence for a similar effect of Intensive Case Management, and for a large effect of family intervention. For quality of life, both EIS and self-management education had a small effect, with moderate quality. The level of research about effective CMH models is therefore substantial. However, several gaps related to innovative CMH not yet covered in meta‐analytic synthesis, need to be filled.